1979
DOI: 10.1172/jci109553
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the synthesis and release of strongly immunosuppressive, noncytotoxic substances by Streptococcus intermedius.

Abstract: A B S T R A C T Products secreted by Streptococcus intermedius were studied for their effects on the immune response. Three different preparations of crude extracellular products from S. intermedius (CEP-Si) were found to have powerful suppressor activity in vitro as shown by inhibition of human lymphocyte proliferation (uptake of [3H]thymidine) and protein synthesis in response to a wide variety of stimulants, including mitogens and antigens, and suppression of plaque formation by human cells in response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…We compared the behavior ofCEP-Si with other previously described noncytotoxic immunosuppressor substances obtained from microorganisms such as streptococcal extracts (2), streptococcal lipoteichoic acid (3), and bacterial enzymes like L-asparaginase (4), L-glutaminase (5), and ribonuclease (6); we concluded that CEP-Si was different from these substances mainly in the time-course of its effects and in the possible specificity of the resulting immunosuppression in relation to the stimulant. Other differences between the in vivo and in vitro effects of CEP-Si and both lipoteiochoic acid and streptococcal extracts were also demonstrated, and preliminary results on the purification of CEP-Si were reported (1). We have now confirmed our preliminary results, and in this report we describe the biochemical characteristics of the highly purified immuinosuppressive material obtained from CEP-Si.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…We compared the behavior ofCEP-Si with other previously described noncytotoxic immunosuppressor substances obtained from microorganisms such as streptococcal extracts (2), streptococcal lipoteichoic acid (3), and bacterial enzymes like L-asparaginase (4), L-glutaminase (5), and ribonuclease (6); we concluded that CEP-Si was different from these substances mainly in the time-course of its effects and in the possible specificity of the resulting immunosuppression in relation to the stimulant. Other differences between the in vivo and in vitro effects of CEP-Si and both lipoteiochoic acid and streptococcal extracts were also demonstrated, and preliminary results on the purification of CEP-Si were reported (1). We have now confirmed our preliminary results, and in this report we describe the biochemical characteristics of the highly purified immuinosuppressive material obtained from CEP-Si.…”
Section: Introductionsupporting
confidence: 78%
“…S. initerniedius was cultured and CEP-Si was obtained by the proceduires described previously in detail (1,7). 1 Abbreviationis uised in this pap)er: CEP-Si, Streptococcus initerintedius; MLC, mixed lymphocyte cultures; PHA, phytohemagglutinin; SDS-PAGE, sodium dodecyl sulphate-polyacrylamide gel electrophoresis; SRBC, sheep erythrocytes; TEMED, N,N,N',N'-tetramethylenediamine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations